PENGESAHAN PERJANJIAN INTERNASIONAL DALAM PERSPEKTIF HUKUM NASIONAL INDONESIA - Setyo Widagdo (Arena Hukum, 2019)
Abstract The ratification of an international treaty is an important action of a nation because it will determine the involvement of that nation in the international agreement. Law No.24 Year 2000 concerning International Treaties regulates about ratification, both in terms of internal (article 9) and external (article 1 number 2). The purpose of this article is to analyze whether ratification of an international agreement according to Law No.24 Year 2000 is â€œapprovalâ€ or â€œconfirmationâ€? And what is the appropriate action or form of such ratification? The results shows that the ratification of an international agreement, if view from an external procedure must be interpreted as a form of â€œconfirmationâ€. Whereas from the internal procedure point of view, ratification must be interpreted as an â€œapproval of the DPRâ€. This can also be interpreted as a